2015
DOI: 10.1093/ehjci/jev185
|View full text |Cite
|
Sign up to set email alerts
|

Strain echocardiographic assessment of left atrial function predicts recurrence of atrial fibrillation

Abstract: AimsWe evaluated if a dispersed left atrial (LA) contraction pattern was related to atrial fibrillation (AF) in patients with normal left ventricular (LV) function, and normal or mildly enlarged left atrium.Methods and resultsWe included 61 patients with paroxysmal AF (PAF). Of these, 30 had not while 31 had recurrence of AF after radiofrequency ablation (RFA). Twenty healthy individuals were included for comparison. Echocardiography was performed in patients in sinus rhythm the day before RFA. LA volume was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 34 publications
3
102
2
4
Order By: Relevance
“…For example, diastolic dysfunction is more strongly linked to LA health than LV health . Additionally, LA function is a strong prognosticator in heart failure, and has been shown to predict the recurrence of atrial fibrillation in patients with normal LV function . In adults, anthracycline exposure is associated with a significant change in LA GLS .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diastolic dysfunction is more strongly linked to LA health than LV health . Additionally, LA function is a strong prognosticator in heart failure, and has been shown to predict the recurrence of atrial fibrillation in patients with normal LV function . In adults, anthracycline exposure is associated with a significant change in LA GLS .…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, LA function is a strong prognosticator in heart failure, 7 and has been shown to predict the recurrence of atrial fibrillation in patients with normal LV function. 8 In adults, anthracycline exposure is associated with a significant change in LA GLS. 9 In survivors of pediatric cancer exposed to anthracyclines, peak negative LA strain, 10 LA reservoir, and LA booster pump function were reduced.…”
mentioning
confidence: 99%
“…A 2D strain analysis enables identification of these phases. Various studies have demonstrated impaired LA global and regional function in patients with paroxysmal AF despite a normal or mildly enlarged LA (8)(9)(10) . As demonstrated by the present study, impairment in the reservoir function was detected even before atrial dilatation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of atrial conduction and/or refractoriness and increased left atrium (LA) size are related to both genesis and maintenance of AF (Jurkko et al, ; Sarvari et al, ) with reciprocal relationship between AF and electrophysiological and/or structural remodelling due to atrial cardiomyopathy (Goette et al, ).…”
Section: Introductionmentioning
confidence: 99%